Quality standards for development evaluation (OECD, 2010)
Based on a broad international consultative process, the DAC Quality S tandards for Development Evaluation are a reference guide to good prac tice in development evaluation. With a view to improving the quality o f evaluation processes and products, and facilitating collaboration, t his reference guide lays out standards for each phase of a typical eva luation process: from defining purpose, to planning, designing, implem enting, reporting, and learning from and using evaluation results.